2016
DOI: 10.1590/0101-60830000000073
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian scientific articles on “Spirituality, Religion and Health”

Abstract: Background: Studies on "Spirituality, religion and health" (R/S) have been increasing worldwide, including in Brazil. Mapping this production can help researchers to understand this field and also to identify gaps in the Brazilian R/S studies. Objective: To analyze the Brazilian scientific articles on "Religion, Spirituality and Health" available on the main electronic databases using a bibliometric approach. Methods: A comprehensive review of four major databases (PubMed, Scopus, BVS and Web of Science) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
(29 reference statements)
0
16
0
19
Order By: Relevance
“…In general, the Brazilian population is very mystical and religious (Schmidt, 2016), which justifies the recent growth of studies in the field of "spirituality, religiosity, and health" in the country (Damiano et al, 2016). It is noteworthy that all participants in our study professed some religion and most of them had low educated (10 out of the 15 mothers only completed elementary school).…”
Section: Psychocultural and Social Issuesmentioning
confidence: 61%
“…In general, the Brazilian population is very mystical and religious (Schmidt, 2016), which justifies the recent growth of studies in the field of "spirituality, religiosity, and health" in the country (Damiano et al, 2016). It is noteworthy that all participants in our study professed some religion and most of them had low educated (10 out of the 15 mothers only completed elementary school).…”
Section: Psychocultural and Social Issuesmentioning
confidence: 61%
“…The study reported a specific protective role of higher religiosity in mental health for highly impulsive participants. It adds new data in a proficuous field in Brazil, studies aiming the association between religion and health 16 . Further studies should investigate this relationship in more representative samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Canada was conducted in 2003 [30]. Research and scientific publications about spirituality have been progressively growing worldwide, and they have also taken big steps in Portugal [31] and in Brazil [32]. The research about spirituality in nursing in Portugal and Brazil usually includes educational aspects [28,33], ethical aspects regarding spiritual interventions [34,35], nursing diagnoses' validation , spiritual needs' assessment, and the validations of instruments [37,38].…”
Section: Introductionmentioning
confidence: 99%